Pioneer in Pediatric Pathology: William A (Bill) Newton Jr (1923–). (March 2019) - Wright, James R; Baker, Peter B; Shimada, Hiroyuki
William A (Bill) Newton Jr practiced pediatric pathology and hematology/oncology at Children's Hospital of Columbus, Ohio, for over 40 years starting in 1952. Newton was an original member of the Pediatric Pathology Club, which preceded the Society for Pediatric Pathology, and was its president from 1968 to 1969. He published important independent observations in pediatric pathology, helped establish systematic cooperative pediatric tumor pathology review by experts, became an acclaimed expert on the diagnosis of rhabdomyosarcoma, was a critical contributor to many pediatric oncology clinical trials, made important early contributions to tumor banking in pediatrics, and trained numerous pediatric pathology and pediatric oncology fellows. Finally, he concluded his career as a humanitarian, leading important volunteer work aimed at improving pediatric cancer care in China. This most interesting pediatric pathologist was simultaneously a Brigadier General in the U.S. Army. Bill Newton's life and career, which is reviewed in detail here, should be of immense interest and an inspiration to the Pediatric & Developmental Pathology readership.